Association between omega-3 index and depersonalization among healthcare workers in a university hospital: a cross-sectional study - Antao, Helena Sofia; Sacadura-Leite, Ema; Aguiar, Pedro; Gois, Carlos; Marques, Jessica; Pombo, Samuel; Figueira, Maria Luisa (Frontiers in Psychiatry, 2024)
Burnout harms workers physical and mental health due to induced brain changes, autonomous nervous system and hypothalamus-pituitary-adrenal axis excessive activation. Although several correlations and risk factors have been identified, the research around burnout biological correlates remains underdeveloped. The omega-3 index has been proposed in mental health as a contributor to identify high risk patients and monitor disease advancements but the evidence on its relationship with burnout is limited. This study is meant to test the hypothesis that the omega-3 index is inversely associated with burnout levels and to discuss its potential as a biological correlate of burnout. It had an observational, cross-sectional design and was carried out at a university hospital center between March 2021 and July 2023. We invited 319 healthcare professionals (doctors and nurses) at the occupational health and emergency departments. The omega-3 index was determined through a prick finger test. Emotional exhaustion, depersonalization and personal accomplishment were measured by the Maslach Burnout Inventory. Descriptive analyses were conducted to examine the participants' characteristics and outcome variables. Means, medians, interquartile ranges and standard deviations were calculated for continuous variables. Frequencies and percentages were obtained for categorical variables. We have used the individual dimensions' scores as continuous data in the evaluation of their relationship with the omega-3 index. The relationship between burnout levels and the omega-3 index was assessed through linear regression analysis.We surveyed 300 subjects (94% response percentage). High emotional exhaustion and depersonalization were reported by 29.9% and 22.1% of participants, respectively; 26.0% reported low personal accomplishment. The mean omega-3 index was 5.75%. The depersonalization score was, on average, 11.132 points higher (95% CI [4.661; 17.603]) in individuals whose omega-3 index was lower than 4%. An omega-3 index below 4% seems to potentially be a biological correlate of depersonalization. Our results contribute to enlarging the knowledge about burnout biological correlates, an area that has been previously signaled as underdeveloped. Omega-3 index should be included in prospective studies that will investigate the evolution of other burnout biological correlates as the syndrome emerges and progresses in subjects at risk.